Chaos in the novel, the novel in the chaos: Herman Melville and his poetics: in search of order (Philologia, 2021)
The aim of this paper is to point to the speciﬁc synthesis of autobiographical, non-ﬁctional, and ﬁctional material in literary works of Herman Melville in which, according to the romantic postulates, the afﬁrmation of different generic conceptions is manifested. The special concentration of the paper is on the early period in Melville’s career in which the ﬁrst novel, Typee: A Peep at Polynesian Life, presents the perfect example of the above stated. In this novel the author parodies the romance as a genre and, after a process of modiﬁcation, ‘places’ it into the inner construction of his literary texts, where it succumbs once more to the speciﬁc laws and especially the horizon of expectation of the reading public in Melville’s time. The manifestations of the generic hibridity are evident on many layers of the text.
Keywords: autobiographical; nonfictional; genre; generic predictability; romance